Adsorption characteristics of layered soil as delay barrier of some organic contaminants: Experimental and numerical modeling. (December 2018) - Dardouri, Sana; Sghaier, Jalila
Abstract: To minimize the contaminant migration in the soil, the use of two and three-layer capillary barriers is proposed as an efficient solution. Indeed, the soil can be used as a physicochemical filter for some pollutants. To discuss the effectiveness of layered soil in the reduction of organic pollutant transport, an experimental and numerical model was developed in this study. The adsorption capacity of the cationic dye, which used as an example of adsorbed organic pollutant, in a soil (sand, clay, silty soil) has been studied in batch and fixed bed column. It was found that the concentration at the column outlet doesn't exceed 4.5% of the initial concentration after 214 days. Due to the presence of a smectite clay layer and three layer capillary barriers, the transport of dye was insignificant because of the high adsorption capacity of clay and silty soil. The experimental results were also confronted with a numerical simulation. A finite element analysis model was employed in this study to predict the coupled process of variably saturated soils by the contaminants transported in runoff. Experimental and numerical results confirm that the water velocity and the kinetic adsorption are inversely proportional through the two and three layer barrier system. Highlights: A three layer capillary barrier is proposed as a solution to pollutant migration. Experimental and numerical models were developed. The effectiveness of layered soil has been discussed in the pollutant transport. The concentration doesn't exceed 4.5% the initial concentration in layered soil. The water velocity and the kinetic adsorption are inversely proportional.